The Influence Of Financial Literacy, Financial Attitude, And Risk Perception On Investment Decisions With Financial Technology As An Intervening Variable in the Generation Z In Semarang City: Pengaruh Literasi Keuangan, Sikap Keuangan, dan Persepsi Risiko terhadap Keputusan Investasi dengan Teknologi Keuangan sebagai Variabel Intervening pada Generasi Z di Kota Semarang - Putri, Reiya haliza; Noni Setyorini; Dhea Rizky Amalia (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to determine the influence of Financial Literacy, Financial Attitude, and Risk Perception on Investment Decisions with Financial Technology as an Intervening Variable (Case Study of Generation Z in Semarang City). The method used in this research is a quantitative method, using primary data with a data collection method using a questionnaire. Hypothesis testing uses the Structural Equation Model (SEM) method with the help of SmartPLS software. The results of this research prove that: (1) financial literacy has a negative effect on investment decisions (2) Financial Attitude has a significant influence on investment decisions (3) Risk Perception has no influence on investment decisions (4) There is a positive and significant influence of financial literacy on financial technology (5) Financial Attitude has a negative effect on financial technology (6) There is a positive and significant influence of risk perception on financial technology (7) There is a positive and significant influence of financial technology on investment decisions (8) Financial Literacy has a negative effect on investment decisions through financial technology as an intervening variable (9) Financial Attitude has a negative effect on investment decisions through financial technology as an intervening variable (10) Risk Perception has a positive and significant effect on investment decisions through financial technology as an intervening variable.